[The French Economic Situation and the State of Finances] - Mangin, Arthur (Quarterly Journal of Economics, 1886)
Journal Article Correspondence Get access Arthur Mangin Arthur Mangin Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 1, Issue 1, October 1886, Pages 91–102, https://doi.org/10.2307/1883113 Published: 01 October 1886